Outcomes in Open Structure Septorhinoplasty. (2nd September 2014) - Sharma, Sunil D.; Jacques, Tom; Abed, Tarik; Gatland, David
Abstract : Objectives: The aim of our study was to look at patient related outcome measures and complications post–open structure septorhinoplasty performed by the same experienced rhinologist and to look at any factors associated with increased risk for requirement of revision surgery. Methods: Retrospective review of case notes of all patients who underwent septorhinoplasty at the same institute, performed by the same rhinologist, between January 2009 and February 2013. Assessment of patient satisfaction was made using the Rhinoplasty Outcomes Evaluation (ROE) tool. Results: One hundred seventy patients were included in the study, with mean follow‐up of 28.2 months. The most common complication was residual deformity (10/170, 5.9%). Eleven patients required further revision nasal surgery (11/170, 6.5%). There was a statistically significant increase in the ROE scores pre‐ and postoperatively in all patients undergoing surgery (19.5 ± 9.41 vs 68.4 ± 23.7, P <. 001). There was a statistically significantly higher rate of revision surgery in patients who had complex surgery (4/16 vs 7/154, P =. 01), a higher rate of nasal tip deformity in the revision surgery group compared with the primary surgery group (10/24 vs 29/146, P =. 03), and a higher rate of augmentation surgery in the revision surgery group compared with the primary surgery group (13/24 vs 40/146, P =.02). Conclusions: Open structure septorhinoplasty results in a significant increase in patient satisfaction. Our rate of revision surgery is lower than the average reported in the literature. The rate of revision surgery is higher in cases judged to be more complex preoperatively.